THE APPLICATION OF LEARNING MODEL COOPERATIVE TYPE TEAMS GAMES TOURNAMENT (TGT) TO IMPROVE ACTIVITY LEARNED MATHEMATICS CLASS VIII C SMP MUHAMMADIYAH PLERET BANTUL YOGYAKARTA - Solikhah Nida; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2017)
Learning centered on teachers caused students less active in following learning math.This study attempts to improve activity learned mathematics through learning model cooperative type Teams Games Tournament ( TGT ) on a student VIII c odd semester SMP muhammadiyah pleret bantul academic year 2016 / 2017. The research is the act of class research ( PTK).A subject in this research is VIIIÂ students class c junior muhammadiyah pleret district bantul odd semester academic year 2016 /2017.Whereas the object investigated in this study is the application of the cooperative model learning type Teams Games Tournament ( TGT ) on grade students VIII C odd semester SMP muhammadiyah pleret academic year 2016 / 2017. The research was done as many as three cycles. Data was gathered using sheets of observation, and an interview .Data analysis used is descriptive qualitative. The result showed that through learning model cooperative type Teams Games Tournament (TGT) could jazz up the activity learned mathematics graders VIII C odd semester SMP muhammadiyah pleret bantul academic year 2016 / 2017. This is apparent from the observation students sheets activity was increasing ever cycle, at the cycle I the percentage of activity students 50,39 % on enough, the percentage of students II activity of 53,88 % on good, the percentage of students III activity of 70,81 % on good. From the pieces, observation activity was also was increasing every cycle. From the interviews obtained information that students interested in general and who love in learning math.